2003
DOI: 10.1097/00006982-200312000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy for Chronic Central Serous Chorioretinopathy

Abstract: ICG-guided PDT performed according to the parameters outlined by the TAP Study seems effective for treating chronic CSC. Further studies are needed to verify treatment safety and the time and rate of recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
215
2
15

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(244 citation statements)
references
References 27 publications
9
215
2
15
Order By: Relevance
“…However, like red laser, PDT also failed to improve the visual outcome, as reported by others as well. 5,6 Canakis et al and later Taban et al have reported improved visual outcome after PDT for chronic CSC, which they correlated with preoperative visual acuity, and recommended early treatment for better results, 14,20 endorsed by others. 5,8,13,15 There is no consensus on how early the 'early' treatment should be applied: foveal atrophy may occur anytime after 4 months of foveal detachment, 15 chronic degenerative changes in macula are likely after 6 months; 5 both result in a poor visual outcome.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, like red laser, PDT also failed to improve the visual outcome, as reported by others as well. 5,6 Canakis et al and later Taban et al have reported improved visual outcome after PDT for chronic CSC, which they correlated with preoperative visual acuity, and recommended early treatment for better results, 14,20 endorsed by others. 5,8,13,15 There is no consensus on how early the 'early' treatment should be applied: foveal atrophy may occur anytime after 4 months of foveal detachment, 15 chronic degenerative changes in macula are likely after 6 months; 5 both result in a poor visual outcome.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, two reports that showed significant visual improvement with PDT in chronic CSC also used FFA rather than ICG, 14,20 considered essential by others. 2,5,6 TTT has been successfully used to treat subfoveal CNV of various aetiologies. [21][22][23] Owing to its thermal nature, TTT may act like conventional photocoagulation in CSC, causing RPE debridement, migration, transformation, and re-proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18] Selecting an appropriate fluence rate avoids collateral damage such as atrophy of the RPE, choroidal ischemia, and development of secondary CNV due to less choriocapillaris damage. [19][20][21] This retrospective study targets on a treatment regimen for CNV in chronic CSCR that has not been described in literature before: a combination of IVR/IVB and ICGAguided PDT with half-fluence rate.…”
Section: Introductionmentioning
confidence: 99%